Eksplorasi Kebutuhan Stakeholders Terhadap Informasi dalam Laporan Audit Pemerintah Daerah - Joko Susilo (Jurnal Akuntansi dan Auditing Indonesia, 2006)
This research’s aim is to know the perception of stakeholders toward information in the published audit report of local government can fulfill their requirement of audit information. This research also to identify the requirement of stakeholders on audit information from local government. The hypothesis of this research is that audit report of local government published by The Audit Board of Indonesia (BPK) has not yet fulfilled the stakeholders’ requirement on information about financial audit, compliance audit, and performance audit.This research’s subjects are stakeholders of local government cover the taxpayer, elector, local government banking, private sector banking, observer body/LSM, personnel educator, governmental officer, political party, and member legislative. Data were collected with the method of purposive sampling with responder in DIY. Statistical methods used is test of mean instrument, correlation test, rank of mean test, and binomial test.Result of statistic test indicates that the information in audit report of local government has not yet fulfilled the stakeholders’ requirement. Correlation test shows the negative relation with the low correlation coefficient among (-0,197 until -0,207). Result of rank of mean test shows the importance of all information in financial audit, compliance audit, and performance audit. Keywords:    exploration-theory of agency, accountability, value for money audit, audit report of local government.